2015
DOI: 10.1039/c5ra13082d
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin modified graphene oxide–magnetic nanocomposite for targeted delivery and pH-sensitive release of stereoisomeric anti-cancer drugs

Abstract: β-cyclodextrin modified graphene oxide-magnetic (MGC) nanocomposite as an innovative drug carrier was the first developed via an effective layer-by-layer-assembly method. Doxorubicin hydrochloride (DOX) and epirubicin hydrochloride (EPI) as model drugs were loaded onto the MGC via π-π stacking, hydrogen bond and hydrophobic interaction. The MGC exhibits remarkably higher loading capacity for DOX (909.09 mg/g) and EPI (781.25 mg/g) than magnetic graphene oxide (MG). The release profiles of drug are pH-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 52 publications
3
28
1
Order By: Relevance
“…[ 32–34 ] The chiral components summarized in Section 2 can be rationally coupled with graphene and the derivatives, which further improve the applicability of graphene materials. Additionally, the result in this study [ 104 ] further evidences the importance of chirality in biological and physiological processes.…”
Section: Chiral Applications Of Chiral Graphene Hybrid Materialssupporting
confidence: 61%
See 2 more Smart Citations
“…[ 32–34 ] The chiral components summarized in Section 2 can be rationally coupled with graphene and the derivatives, which further improve the applicability of graphene materials. Additionally, the result in this study [ 104 ] further evidences the importance of chirality in biological and physiological processes.…”
Section: Chiral Applications Of Chiral Graphene Hybrid Materialssupporting
confidence: 61%
“…The study establishes an efficient nanoplatform for targeted delivery and controlled release of chiral drugs for biomedical applications. [ 104 ] Enantioselective effects in chiral drug delivery has become one of the research themes in pharmaceutical community. [ 263,264 ] Owing to the chiral nature of the frequently used carriers and/or excipients (e.g., starch and dextrin) and the special chiral environment inside human body, chiral drugs may undergo specific enantioselective interactions with the chiral carriers and human body.…”
Section: Chiral Applications Of Chiral Graphene Hybrid Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity test on the cells indicated that MGC has a lower toxic effect than MG whereas MGC/epirubicin showed a stronger lethal effect on MCF-7 cells. 107 In a recent work, it was proved that the decoration of GO nanosheets by magnetic iron nanoparticles followed by functionalization by chitosan/sodium alginate (CS/SA) leads to the formation of a versatile nanocarrier which can load a high amount of DOX, release it in a low pH environment and enhance cancer cell killing via photothermal therapy (PTT). 108 In a similar study, the triple responsive (pH, thermal and magnetic) GO nanohydrogel was developed and its DOX release ability was examined in the presence and absence of the magnet.…”
Section: Magnetically Released Drug From Graphene Nanocarriersmentioning
confidence: 99%
“…The toxicity test on the cells indicated that MGC has a lower toxic effect than MG whereas MGC/epirubicin showed a stronger lethal effect on MCF-7 cells. 107 …”
Section: Drug Delivery Applicationsmentioning
confidence: 99%